Bubbles O2 factory: a digital solution for batch data excellence - Azlin, Awfa; Muhammad Aris, Nurul Izzaty; Hassan, Mohd Khairul Azmi (KICT Publishing, 2024)
This document proposes a web-based batch data management system to address Bubbles O2's current struggles with manual data entry, limited real-time monitoring, and inefficient data retrieval. These shortcomings prevent them from tracking production, analyzing trends, and making data driven decisions. The proposed solution, built using the Laravel framework, tackles these issues by allowing bulk data import, facilitating real-time visualization of key metrics on a centralized dashboard, and enabling users to easily search, filter, and export data through user-friendly interfaces. These improvements are expected to yield significant benefits, including enhanced data accuracy, improved real-time analysis capabilities, increased operational efficiency, and better reporting and compliance, ultimately granting Bubbles O2 a competitive edge through the power of real-time data and streamlined operations.